Collaborative Weeding of an Engineering Collection: Two Perspectives. Issue 4 (2nd October 2018) - Busch, Heidi; Nance, Jim; Teague, Jared
Abstract: Weeding an academic library can often be contentious and easily put off for years. However, in technical fields the collection should be evaluated frequently. The collection should serve faculty for course development and research while providing the students with resources for coursework. The authors present collaborative weeding of the engineering collection at the University of Tennessee at Martin's Paul Meek Library. The procedure incorporated spreadsheets for identification of items as candidates for weeding. This allowed the library liaison to reduce engineering faculty workload in the process, increasing faculty participation and creating a collection more reflective of the needs of faculty and students.